d-Histidine inhibits Streptococcus mutans growth as a potential anti-caries agent - Liuchang Yang; Yuxing Chen; Yaqi Chi; Xiaolin Chen; Yiran Zhao; Mingrui Zhang; Xuemeng Wang; Yongliang Li; Jie Nie; Xiaoyan Wang (Journal of Oral Microbiology, 2025)
Background Dental caries is a bacterial-mediated infectious disease that affects the hard tissues of the tooth, with Streptococcus mutans being the primary cariogenic pathogen due to its robust biofilm-forming ability. Controlling biofilm formation is essential for caries prevention. Recent studies have indicated that D-amino acids, which are not incorporated into proteins, play regulatory roles in bacterial processes such as growth inhibition and biofilm dispersal. However, whether D-amino acids can inhibit the growth of S. mutans remains controversial. This study aimed to investigate the effects of D-amino acids on S. mutans growth and biofilm formation in vitro, as well as their anti-caries efficacy in a rat caries model.Materials and Methods This study utilized Streptococcus mutans UA159 to screen 15 D-amino acids for growth inhibition, identifying D-histidine (D-His) as the most effective. Minimum inhibitory concentration, growth curves, biofilm assays, and transcriptomic analysis were performed in vitro. Anti-caries efficacy was evaluated in a rat model using Micro-CT and Keyes scoring.Results D-His significantly inhibits the planktonic growth of S. mutans and delays biofilm formation, particularly in the early stages. Furthermore, RNA sequencing revealed 417 upregulated genes and 394 downregulated genes in D-His-treated S. mutans, with significant alterations in pathways related to carbohydrate utilization, protein biosynthesis, and transmembrane transport. Moreover, D-His exhibited effective caries prevention in an in vivo rat model.Conclusion These findings suggest that D-His has potential as an anti-caries agent by targeting S. mutans growth and biofilm dynamics.